The Effect Of Anemia In Pregnancy On Maternal Outcomes - Setyaningsih, Dewi; Mindarsih, Eko; Wijayanti, Henny Noor; Novika, Almira Gitta; Wahyuningsih, Melania; Susanti, Santi (MEDIA ILMU KESEHATAN, 2025)
Background: Nutritional problems in pregnant women are still one of the health challenges. One of the monitoring of nutritional status can be done by looking at the status of iron deficiency anemia. Anemia is still a global health problem that can have an impact on maternal and fetal outcomes.Objective: To determine the effect of hemoglobin levels in pregnant women on maternal outcomes.Methods: The method used is quantitative with a cross-sectional approach and data analysis using chi square test.Results: There was no effect between hemoglobin levels and sectio caesarea (P-value 0.427>0.05), There was no effect between hemoglobin levels and induction of labor (P-value 1.00>0.05), There was no effect between anemia status and hemmorharge (P-value 1.00>0.05), There was no effect between hemoglobin levels and premature (P-value 0.648>0.05), There was no effect between anemia status and prolonged labor (P-value 0.352>0.05), There was no effect between hemoglobin levels and premature rupture of membrane (P-value 1.00>0.05) and There was no effect between hemoglobin levels and preeclampsia (P-value 1.00>0.05).Conclusion: There was no effect of hemoglobin levels on maternal outcome.